Volume 8: 14th Design for Manufacturing and the Life Cycle Conference; 6th Symposium on International Design and Design Educati 2009
DOI: 10.1115/detc2009-87749
|View full text |Cite
|
Sign up to set email alerts
|

Framing Sustainability in Human-Centered Product Design

Abstract: Engineers today have access to a myriad of tools for developing sustainable products that have minimal environmental impact. Although consumer interest in sustainability is increasing, it is still not foremost on the minds of many consumers. Engineers are thus faced with the dilemma of developing sustainable solutions for consumers who may not yet want or be able to articulate sustainability needs. We explore this issue by examining user research conducted by students in a graduate-level product design course.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…MacDonald and She summarized seven cognitive concepts for successful sustainable design, including Responsibility, Complex decision making, Decision heuristics, Altruism-sacrifice link, Trust, Cognitive dissonance, and Motivation, in an effort to build the connection between the behavior and design [16]. Oehlberg et al collected user research from a graduate-level design course to identify what sustainability means to users and explored how to align user needs with product sustainability [17]. Lilley developed three categories of strategies for designing for sustainable behavior: eco-feedback, which guides behavior changes by informing users of resource use; behavior steering, which encourages users to behave in ways embedded in the design itself; and persuasive technology, which employs persuasive methods to change what people do without their knowledge or consent [18].…”
Section: Related Workmentioning
confidence: 99%
“…MacDonald and She summarized seven cognitive concepts for successful sustainable design, including Responsibility, Complex decision making, Decision heuristics, Altruism-sacrifice link, Trust, Cognitive dissonance, and Motivation, in an effort to build the connection between the behavior and design [16]. Oehlberg et al collected user research from a graduate-level design course to identify what sustainability means to users and explored how to align user needs with product sustainability [17]. Lilley developed three categories of strategies for designing for sustainable behavior: eco-feedback, which guides behavior changes by informing users of resource use; behavior steering, which encourages users to behave in ways embedded in the design itself; and persuasive technology, which employs persuasive methods to change what people do without their knowledge or consent [18].…”
Section: Related Workmentioning
confidence: 99%
“…He categorizes user experience into three levels: instinct, behaviour, and reflection. Norman emphasizes a 'human-centred' approach in product design, advocating for a focus on user needs and psychology [ 21 , 22 ]. This approach underscores the importance of fundamental product aspects such as functionality, usability, and safety while advocating for a comprehensive consideration in product design that encompasses functionality, ease of use, originality, artistic value, and engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Engineering education has incorporated teamwork as a key component of the curriculum to prepare engineers for industry and to achieve a number of professional learning outcomes, including developing interdisciplinary teamwork skills [19]- [21], cultivating communication skills [22], and improving innovation and creativity [21], [23]. Research on teams in engineering education has shown that there can be both positive and negative outcomes for students working on these teams [24], [25].…”
Section: Background 21 Teams In Engineering Educationmentioning
confidence: 99%